Corrected whole blood biomarkers – the equation of Dill and Costill revisited. Issue 12 (25th June 2018) - Matomäki, Pekka; Kainulainen, Heikki; Kyröläinen, Heikki
Abstract: An exercise bout or a dehydration often causes a reduction in plasma volume, which should be acknowledged when considering the change in biomarkers before and after the plasma changing event. The classic equation from Dill and Costill (1974, J. Appl. Physiol., 37, 247–248) for plasma volume shift is usually utilized in such a case. Although this works well with plasma and serum biomarkers, we argue in this note that this traditional approach gives misleading results in the context of whole blood biomarkers, such as lactate, white cells, and thrombocytes. In this study, we demonstrate that to calculate the change in the total amount of circulating whole blood biomarker, one should utilize a formula BM post BM pre × H b pre H b post − 1 . Here Hb and BM are, respectively, the concentrations for the hemoglobin and for the inspected whole blood biomarker before (pre) and after (post) the plasma changing incident. Abstract : In this study, a correction formula, induced by a plasma change, is derived for the whole blood biomarkers. Usually utilized correction formula from Dill & Costill is applicable only for the plasma and serum biomarkers. The difference between the two formulas is discussed.